The needs of members of the families of general hospital inpatients - Lucchese, Ana Cecília; Citero, Vanessa de Albuquerque; Marco, Mario Alfredo De; Andreoli, Sergio Baxter; Nogueira-Martins, Luiz Antonio (São Paulo Medical Journal, 2008)
CONTEXT AND OBJECTIVE: The needs of members of the families of intensive care unit patients have been studied, but little is known about the needs of members of the families of general hospital inpatients, especially patients with chronic diseases. The aim of this study was to identify the needs of members of the families of general hospital inpatients and investigate associations between these needs and the patients’ clinical and psychiatric profi les. DESIGN AND SETTING: Descriptive study, in a public teaching hospital. METHODS: A random sample of 47 patients and members of their families was studied. Family members’ needs were investigated using the critical care family needs inventory and the patients’ clinical profi les were investigated using the hospital anxiety and depression scale, confusion assessment method and Karnofsky performance status. The frequencies of family members’ needs were described and the patients’ clinical and psychiatric characteristics were correlated with the needs using the chi-squared test. RESULTS: Chronic patients predominated and the needs for reassurance and information were indicated as the most important by all members of their families. No associations were found between the patients’ characteristics and the needs of members of their families during the hospitalization. CONCLUSIONS: The needs indicated by members of the families of general hospital inpatients were similar to those of members of the families of patients in intensive care units: they considered it very important to be reassured and kept informed throughout the hospitalization.